Introduction to the humanities : a holistic approach - Menoy, Jesus Z. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2009)
This book is a encompasses all the major fields of art. The phrase "holistic approach" was used as a subtitle because with the help of this book, the teacher will be able to approach the teaching of Humanities holistically.
Dedication -- Acknowledgements -- Preface vii List of figures -- Chapter 1. Introduction -- Chapter 2. Painting -- Chapter 3. Sculpture -- Chapter 4. Architecture -- Chapter 5. Music -- Chapter 6. Dance -- Chapter 7. Drama -- Chapter 8. Poetry -- Chapter 9. Prose -- Appendix A- Figures of Speech -- Appendix B-Orders of Greek Architecture -- Bibliography.
Includes bibliographical references.
Keywords: HUMANITIES -- ARTS -- PERFORMING ARTS